Re-defining Our Approaches to Extreme Poverty: An Attempt to Disrupting Contemporary Poverty Alleviation Approaches through Inspiration Economy Project- A Case Study - Buheji, Mohamed (International Journal of Economics and Financial Issues, 2019)
The paper provides a comparative review and analysis between the approaches of poverty and extreme-poverty solutions, emerging in literature and from Inspiration Economy Project Poverty Labs (IEP-PLs); carried over three years. The paper focuses on the differentiation that current ‘extreme poverty’ elimination requires. Notably, the models were evaluated about the changes from different perspectives that influence directly or indirectly the quality of life of the poor, or proactively keep him away from the poverty line. More diagnosis of the challenges on how to deal with poverty mechanisms and constructs were reflected in different proposed approaches, as part of the paper discussion. The implications of the paper emphasis on future structural factors and especially with the emerging work of behavioural economics and inspiration labs. The recommendations are drawn based on the new different approaches shown to be of influence on the ‘extreme poverty’ policies and their ways of empowerment. Keywords: Extreme-Poverty, Models for Poverty Elimination, Poverty Alleviation JEL Classification: D6 DOI: https://doi.org/10.32479/ijefi.8053